High fat diet induces gastric production of fibroblast growth factor 23 (FGF23) - Widmayer, Patricia; Feger, Martina; Meier, Leonie; Wagner, Andreas H.; Föller, Michael (International journal of obesity, 2025)
A high fat diet (HFD) leads to lesions of the gastric epithelium and causes a proinflammatory environment. Fibroblast growth factor 23 (FGF23), a bone hormone, regulates renal phosphate and vitamin D metabolism. Under pathophysiological conditions production of FGF23 is stimulated. HFD feeding elevates serum FGF23 levels through inflammation.